Pengaruh pemberian bahan organik terhadap perubahan sifat kimia Andisol, pertumbuhan dan produksi gandum (Triticum eastivum L.) - Irawan, Ahmad; Jufri, Yadi; Zuraida, Zuraida (-)
The study is look at the effect of various doses of the chemical properties of organic materials Andisol, growth and production of wheat. This study was conducted in March to June 2013 in the village Tunyang, Timang Gajah, Bener Meriah province of Aceh and continued in Soil Chemistry Laboratory Faculty of Agriculture, Unsyiah, Darussalam Banda Aceh. This experiment used a randomized block design (RBD) with 10 treatments and 3 replications. experiments conducted in this study were: control, manure 10 tons ha-1, manure 20 tons ha-1, manure 30 tons ha-1, compost 10 tons ha-1, compost 20 tons ha-1, compost 30 tons ha-1, 10 tons of manure ha-1 + compost 10 tons ha-1, manure 20 tons ha-1+ compost 10 tons ha-1, 20 tons of manure ha-1+ compost 20 tons ha-1. These results indicate that increase of organic material does not change the status of pH, C-organic, N-total and P-total planted wheat Andisol. increase of organic materials can improve status P-available and P-retention in Andisol. Highest result the addition of organic material encountered increase manure 30 tons ha-1.